Phellinus linteus Mycelium Alleviates Myocardial Ischemia-Reperfusion Injury through Autophagic Regulation - Su, Hsing-Hui; Chu, Ya-Chun; Liao, Jiuan-Miaw; Wang, Yi-Hsin; Jan, Ming-Shiou; Lin, Chia-Wei; Wu, Chiu-Yeh; Tseng, Chin-Yin; Yen, Jiin-Cherng; Huang, Shiang-Suo (Frontiers in Pharmacology, 2017)
The incidence of myocardial ischemia-reperfusion (IR) injury is rapidly increasing around the world and this disease is a major contributor to global morbidity and mortality. It is known that regulation of programmed cell death including apoptosis and autophagy reduces the impact of myocardial IR injury. In this study, the cardioprotective effects and underlying mechanisms of Phellinus linteus (Berk. & Curt.) Teng, Hymenochaetaceae (PL), a type of medicinal mushroom, were examined in rats subjected to myocardial IR injury. The left main coronary artery of rats was ligated for 1 h and reperfused for 3 h. The arrhythmia levels were monitored during the entire process and the infarct size was evaluated after myocardial IR injury. Furthermore, the expression levels of proteins in apoptotic and autophagic pathways were observed. Pretreatment with PL mycelium (PLM) significantly reduced ventricular arrhythmia and mortality due to myocardial IR injury. PLM also significantly decreased myocardial infarct size and plasma lactate dehydrogenase level after myocardial IR injury. Moreover, PLM administration resulted in decreased caspase 3 and caspase 9 activation and Bcl-2/Bax ratio. Phosphorylation level of AMPK was elevated while mTOR level was reduced. Becline-1 and p62 levels decreased. These findings suggest that PLM is effective in protecting the myocardium against IR injury. The mechanism involves mediation through suppressed pro-apoptotic signaling and regulation of autophagic signaling, including stimulation of AMPK-dependent pathway and inhibition of beclin-1-dependent pathway, resulting in enhancement of protective autophagy and inhibition of excessive autophagy.